Synthesis and Analysis of PVC Selective Membrane for Determination of Diazepam Based on Bulk Molecular Imprinted Polymer - Emad, Maryam; Al-Bayati, Yehya Kamal (Iraqi Journal of Science, 2025)
study developed two electrodes using molecularly imprinted polymers (MIP) for the selective recognition of Diazepam (DZP). Ethylene glycol dimethacrylate (EGDMA) was employed as the cross-linking monomer to polymerize allyl bromide, which acted as the functional monomer. DZP was used as the template molecule during the polymerization process to introduce recognition sites in the polymer matrix complementary to its size, shape and functional groups. For comparison, non-imprinted polymers (NIP) were also synthesized using an identical combination of EGDMA and Allyl bromide as the MIP, but without the incorporation of the DZP template. Evaluations are conducted on the slop is 29.31258 and 25.818933, linearity range (M) 5×10-5-1×10-2,5×10-5-1×10-2, correlation coefficient 0.9964,0.9994 and the detection limit (M)5.5×10-6 - 5×10-6 relatively for DIA-MIP electrodes. Selectivity tests were performed for the interfering cations Al3+, Ca2+ and K+, which showed no inhibition of diazepam detection by the proposed electrode. The generated MIP electrode exhibited promising analytical characteristics, such as good selectivity against common interfering species.